Investigating the effects of Pirfenidone on TGF-β1 stimulated non-SMAD signaling pathways in Dupuytren’s disease -derived fibroblasts - Chaoming Zhou; Yael Zeldin; Mark E. Baratz; Sandeep Kathju; Latha Satish (BMC Musculoskeletal Disorders, 2019)
Abstract Background Dupuytren’s disease (DD) is a progressive, debilitating condition of the hand that can eventually cause contractures of the affected fingers. Transforming growth factor- β1 (TGF-β1) has been reported to play a key role in DD pathology. Increased expression of TGF-β1 has shown to be the main stimulator of myofibroblast activity and in DD contractures. Pirfenidone (PFD), a small active molecule possess the ability to inhibit TGF-β1-mediated action in various fibrotic disorders. Our recent published findings show that PFD reduced TGF-β1-mediated cellular functions implicated in DD through SMAD signaling pathways. In the present study, the effect of PFD on TGF-β1-mediated non-SMAD signaling pathways were investigated in both carpal tunnel (CT) - and DD-derived fibroblasts. Methods Fibroblasts harvested from Dupuytren’s disease (DD) and carpal tunnel (CT) tissues were cultured in the presence or absence of TGF-β1 (10 ng/ml) and/or PFD (800 μg/ml). Cell lysates were analyzed using Western blots. Equal amounts of proteins were loaded to determine the phosphorylation levels of phosphatidylinositol-3 kinase (PI3K/AKT), extracellular regulated kinases (ERK1/2), p38 mitogen-activated protein kinase and Rho family related myosin light chain (MLC). Results We show that the TGF-β1-induced phosphorylation of AKT was significantly decreased by the addition of PFD (800 μg/mL) in both CT- and DD-derived fibroblasts. Interestingly, there was no significant difference in the phosphorylation levels of both ERK and p38 on TGF-β1- induced cells in both CT-and DD-derived fibroblasts. But, PFD significantly decreased the TGF- β1-induced phosphorylation levels of ERK1/2 in both CT- and DD- cells. In contrast, PFD significantly decreased the basal and TGF- β1-induced phosphorylation levels of p38 in DD-derived fibroblasts. TGF- β1-induced phosphorylation levels of MLC was decreased by PFD in DD-derived fibroblasts. Conclusions These in-vitro results indicate for the first time that PFD has the potential to inhibit TGF-β1-induced non-SMAD signaling pathways in both CT- and DD-derived fibroblasts but pronounced statistically significant inhibition on all molecules was observed only in DD-derived fibroblasts. Our previous studies show that PFD can inhibit TGF-β1- induced SMAD signaling pathway proteins, namely p- SMAD2/SMAD3. These broad and complementary actions suggest PFD as a promising candidate to inhibit the TGF-β1- mediated molecular mechanisms leading to DD fibrosis.